Computational study of 3-thiophene acetic acid: Molecular docking, electronic and intermolecular interactions investigations. (June 2020) - Ben Issa, Takoua; Sagaama, Abir; Issaoui, Noureddine
Graphical abstract: Highlights: The optimized was computed using DFT method. DFT and TDDFT calculations have been incorporated for detailed analysis. The intermolecular interactions were analyzed by AIM, NBO, RDG and Hirshfeld surfaces. Inhibitor activity of 3-TAA with human MOA A and B is analyzed via molecular docking. Abstract: The present work undertakes the structural and electronic properties of 3-thiophene acetic acid (abbreviated as 3-TAA) monomer and dimer. DFT calculations were performed using B3LYP functional in combination with the aug-cc-pVTZ basis set. The optimized structural parameters were found to be in a good agreement with experimental molecular geometry. The stability of the crystal packing was ensured by OH⋯O, C-H⋯O and CH⋯S intermolecular interactions. All the Non covalent interactions were deeply studied in terms of their topological parameters, Hirshfeld surface (HS) analysis and reduced density gradient (RDG) analysis. The electronic properties of the investigated compound have been performed using time dependent density functional theory (TD-DFT) and discussed through its correspondant HOMO, LUMO and excitation energy values. Likewise, the reactivity of 3-TAA was discussed in terms of several thermodynamic parameters. In addition, the molecular electrostatic potential (MEP) surface has been performed and discussed in terms of color distribution. In addition, the natural bond orbital (NBO) analysis was used to investigate the electronic charge transfer into the molecule. Harmine, Clorgyline, Isatin, zonisamide and our title compound including are known with their competitive inhibitory activity on Human monoamine oxidase, commonly named MAO A and B. This enzyme is a critical enzyme in the degradative deamination of biogenic amines throughout the body. Thus, molecular docking behaviors of 3-TAA are computed and compared to the results found for Harmine, Clorgyline, Isatin, zonisamide ligands.